A European study on decellularized homografts for pulmonary valve replacement: initial results from the prospective ESPOIR Trial and ESPOIR Registry data. (15th March 2019) - Boethig, Dietmar; Horke, Alexander; Hazekamp, Mark; Meyns, Bart; Rega, Filip; Van Puyvelde, Joeri; Hübler, Michael; Schmiady, Martin; Ciubotaru, Anatol; Stellin, Giovanni; Padalino, Massimo; Tsang, Viktor; et al.
Abstract: OBJECTIVES: Decellularized pulmonary homografts (DPH) have shown excellent results for pulmonary valve replacement. However, controlled multicentre studies are lacking to date. METHODS: Prospective European multicentre trial evaluating DPH for pulmonary valve replacement. Matched comparison of DPH to bovine jugular vein (BJV) conduits and cryopreserved homografts (CH) considering patient age, type of heart defect and previous procedures. RESULTS: In total, 121 patients (59 female) were prospectively enrolled (August 2014–December 2016), age 21.3 ± 14.4 years, DPH diameter 24.4 ± 2.8 mm. No adverse events occurred with respect to surgical handling; there were 2 early deaths (30 + 59 years) due to myocardial failure after multi-valve procedures and no late mortality (1.7% mortality). After a mean follow-up of 2.2 ± 0.6 years, the primary efficacy end points mean peak gradient (16.1 ± 12.1 mmHg) and regurgitation (mean 0.25 ± 0.48, grade 0–3) were excellent. One reoperation was required for recurrent subvalvular stenosis caused by a pericardial patch and 1 balloon dilatation was performed on a previously stented LPA. 100% follow-up for DPH patients operated before or outside the trial ( n = 114) included in the ESPOIR Registry, age 16.6 ± 10.4 years, diameter 24.1 ± 4.2 mm, follow-up 5.1 ± 3.0 years. The combined DPH cohort, n = 235, comprising both Trial and Registry data showed significantly better freedom from explantation (DPH 96.7 ± 2.1%, CH 84.4 ± 3.2%, P = 0.029 and BJV 82.7 ± 3.2%, P = 0.012) and less structural valve degeneration at 10 years when matched to CH, n = 235 and BJV, n = 235 (DPH 61.4 ± 6.6%, CH 39.9 ± 4.4%, n.s., BJV 47.5 ± 4.5%, P = 0.029). CONCLUSIONS: Initial results of the prospective multicentre ESPOIR Trial showed DPH to be safe and efficient. Current DPH results including Registry data were superior to BJV and CH. Trial registration clinicaltrials.gov identifier: NCT 02035540.